2019
DOI: 10.1103/physrevfluids.4.033401
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-induced thermal instabilities in supercritical fluids in the absence of gravity

Abstract: Supercritical fluids (SCFs) are known to exhibit anomalous behaviour in their thermophysical properties such as diverging compressibility and vanishing thermal diffusivity on approaching the critical point. This behaviour leads to a strong thermo-mechanical coupling when SCFs are subjected to simultaneous thermal perturbation and mechanical vibration. The behaviour of the thermal boundary layer (TBL) leads to various interesting dynamics such as thermo-vibrational instabilities, which become particularly osten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In this study, the fluid is far from the mixture's critical point so the isothermal compressibility is relatively low (between 10 −8 and 10 −9 P a −1 ). The comparison of simulations between an incompressible and a compressible formulation [14,15] has shown that the results were very close. Because CPU time is much lower with the incompressible formulation, we consider in this study the following incompressible model for the continuity and Navier-Stokes equations, it reads [16,17]:…”
Section: Hydrodynamicsmentioning
confidence: 84%
“…In this study, the fluid is far from the mixture's critical point so the isothermal compressibility is relatively low (between 10 −8 and 10 −9 P a −1 ). The comparison of simulations between an incompressible and a compressible formulation [14,15] has shown that the results were very close. Because CPU time is much lower with the incompressible formulation, we consider in this study the following incompressible model for the continuity and Navier-Stokes equations, it reads [16,17]:…”
Section: Hydrodynamicsmentioning
confidence: 84%
“…The periodic stripe patterns found in supercritical CO 2 in the experiments of Beysens et al [21] were the first observation of the frozen wave instability in weightlessness; these studies of near-critical fluids were continued on ground using magnetic compensation [22,23]. More recent work [24] on supercritical fluids in microgravity examined thermovibrational instabilities, including the influence of finite-size effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as the flow is isothermal the thermo-compressible effects are negligible. The comparison of simulations between an incompressible formulation with variable density and a full compressible formulation [22,23] has shown that the results were very close. As the CPU time was optimized within the incompressible formulation, as described in the numerical methodology section, we considered this formulation to solve the hydrodynamics phenomena.…”
Section: Governing Equations Of the Fluid Mixingmentioning
confidence: 88%